Critters Of The Night / Zombies Don't Do Windows - Erica Farber (U.S.A., 1996)
There's no April freshness at the Pinch family's house. Their new cleaning lady smells disgusting. But that's pretty normal...for a zombie! And she's turning everyone else in Critter Falls into zombies, too. It's up to the Howls to stop her--without being eaten alive!
Keywords: Fiction -- Fiction